GREEN ECONOMY AS THE FOUNDATION OF SUSTAINABLE DEVELOPMENT: GLOBAL PERSPECTIVES AND NATIONAL STRATEGIES - Eshboyeva , Madina; Eshboyev , Temur; Saitov , Sirojiddin (Scientific practical conference, 2025)
The transition towards a green economy has become one of the most pressing priorities in the modern era of global socio-economic development. Unlike the traditional growth model, which often relies on intensive exploitation of natural resources, the green economy emphasizes sustainability, inclusiveness, and resilience. It integrates economic progress with environmental protection and social justice, aiming to reduce ecological risks and address climate change while enhancing human well-being. This article provides an in-depth exploration of the theoretical foundations of the green economy, its alignment with the United Nations Sustainable Development Goals (SDGs), the multiple benefits it offers, the structural challenges it faces, and selected global case studies. The paper argues that the green economy is not merely an option but the fundamental basis of sustainable development, offering a pathway that reconciles prosperity with environmental stewardship.